Genistein prevents isoproterenol-induced cardiac hypertrophy in rats - Maulik, Subir Kumar; Prabhakar, Pankaj; Dinda, Amit Kumar; Seth, Sandeep (Canadian journal of physiology and pharmacology, 2012)
Genistein, an isoflavone and a rich constituent of soy, possesses important regulatory effects on nitric oxide (NO) synthesis and oxidative stress. Transient and low release of NO by endothelial nitric oxide synthase (eNOS) has been shown to be beneficial, while high and sustained release by inducible nitric oxide synthase (iNOS) may be detrimental in pathological cardiac hypertrophy. The present study was designed to evaluate whether genistein could prevent isoproterenol-induced cardiac hypertrophy in male Wistar rats (150–200 g, 10–12 weeks old) rats. Isoproterenol (5 mg·(kg body weight) –1 ) was injected subcutaneously once daily for 14 days to induced cardiac hypertrophy. Genistein (0.1 and 0.2 mg·kg –1 , subcutaneous injection once daily) was administered along with isoproterenol. Heart tissue was studied for myocyte size and fibrosis. Myocardial thiobarbituric acid reactive substances (TBARS), glutathione (GSH), superoxide dismutase (SOD), catalase levels, and 1-OH proline (collagen content) were also estimated. Genistein significantly prevented any isoproterenol-induced increase in heart weight to body weight ratio, left ventricular mass (echocardiographic), myocardial 1-OH proline, fibrosis, myocyte size and myocardial oxidative stress. These beneficial effects of genistein were blocked by a nonselective NOS inhibitor ( L -NAME), but not by a selective iNOS inhibitor (aminoguanidine). Thus, the present study suggests that the salutary effects of genistein on isoproterenol-induced cardiac hypertrophy may be mediated through inhibition of iNOS and potentiation of eNOS activities.